New perspectives on Old Princeton, 1812-1929
1 online resource (viii, 255 pages).
Keywords: "This book focuses on Princeton Theological Seminary and the theologians who taught there from the time of its founding in 1812 to the time of its reorganization in 1929. It confronts the standard assessment of Old Princeton in the historiography of North American evangelicalism and sets out why a new paradigm is needed. The volume critically engages with the 'Ahlstrom thesis' and other more recent scholarship concerning Old Princeton's relationship to the Scottish intellectual tradition. The contributions seek to move beyond Old Princeton's alleged indebtedness to Enlightenment thought and advance a more constructive reading of the Old Princetonians, their theology, and their place in the American evangelical experience. The book offers a fresh and more accurate assessment of the theological and philosophical assumptions that held sway at Old Princeton and through the seminary to the American continent and beyond. It will appeal to scholars interested in theology, religious history and intellectual history"--